IMPLEMENTASI KURIKULUM 2013 DALAM PEMBENTUKAN AKHLAK DI YAYASAN PERGURUAN AL-IHSAN MERUYA UTARA, JAKARTA BARAT - Ibnu Ilkoini (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2021)
This research is a field research with a descriptive qualitative approach. The implementation Curriculum 2013 in shaping the morals of students at the North Meruya Al-Ihsan Education Foundation, In the Curriculum 2013 there are several elements of competence. the core in it is by using the sentence KI (Core Competence) KI 1, KI 2, KI 3, KI 4, KI 1 is a Spiritual Attitude, KI 2 is a Social Attitude, KI 3 is Knowledge (cognitive), and KI 4 is a skill (Psychomotor) . The formation of morals in these competencies is in KI 1 and KI 2. In KI 1 it encourages students to worship and in worship to have manners that must be obeyed when they want to carry out and when the worship takes place, because in essence when someone is worshiping someone without realizing it was facing and complaining to Allah SWT. Whereas in KI 2 it is a social attitude, the social attitude in question is the attitude or morals of a person to others in socializing. So the implementation curriculum 2013 in education is very important for the moral formation of students because basically curriculum 2013 features active, innovative, creative and noble character in the behavior of everyday life. The results of the implementation of the 2013 curriculum in the formation of morals at the al-ihsan college foundation have gone well and the results have formed students who have noble morals, such as filial piety, honesty, responsibility, etc